Crise do capital e o desmonte da Previdência Social no Brasil - Lourenço, Edvânia Ângela De Souza [UNESP]; Lacaz, Francisco Antonio De Castro; Goulart, Patrícia Martins (Cortez Editora Ltda, 2017)
This article discusses the Social Security System (SSS) (PEC n. 287/2016), with particular attention to the reduction of workers' rights, under the justification of the SSS deficit. The analysis, based in legal documents and bibliography revision, includes the reformists measures adopted also by the Fernando Henrique, Lula, and Dilma governments in relation to SSS. It is concluded that the measures, like a real counter-reform are based on the logic of the private sector, and transforms social rights into goods and beckons for the drastic reduction of such rights.

Discute-se a reforma em curso relativa ao desmonte da Previdência Social (PS) (PEC n. 287/2016), com atenção especial para a redução dos direitos dos trabalhadores, sob a justificativa do déficit da PS. Trata-se de um ensaio teórico, a partir de pesquisa bibliográfica e documental, cuja análise abarca as medidas reformistas também dos governos Fernando Henrique, Lula e Dilma. Observa-se que tais medidas evidenciam que, como uma real contrarreforma, regem-se pela lógica do setor privado, transformando direitos sociais em mercadorias com a redução drástica desses direitos.
Crisis of the capital and dismantling of Social Security in Brasil
Keywords: Work; Counter-reform; Social Security System; Trabalho; Contrarrefor ma; Previdência Social